2010
DOI: 10.3748/wjg.v16.i48.6087
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective actions of melatonin: Possible mediation by melatonin receptors

Abstract: Melatonin, the hormone of darkness and messenger of the photoperiod, is also well known to exhibit strong direct and indirect antioxidant properties. Melatonin has previously been demonstrated to be a powerful organ protective substance in numerous models of injury; these beneficial effects have been attributed to the hormone's intense radical scavenging capacity. The present report reviews the hepatoprotective potential of the pineal hormone in various models of oxidative stress in vivo, and summarizes the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 177 publications
(225 reference statements)
2
46
0
4
Order By: Relevance
“…Despite the enormous amount of data supporting the idea of melatonin as a liver protective agent, it should be noted that there are also other reports that have indicated no hepato-protective effect of melatonin to the effect of 2-nitropropane and ethanol in rat liver, which supports our results (Mathes, 2010). On the other hand, lower rates of ROS generation in the liver and decreases in mitochondrial energy metabolism has been reported in rats subjected to hypobaric hypoxia (Costa et al, 1993;NouetteGaulain et al, 2011 andFarías et al, 2005a).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite the enormous amount of data supporting the idea of melatonin as a liver protective agent, it should be noted that there are also other reports that have indicated no hepato-protective effect of melatonin to the effect of 2-nitropropane and ethanol in rat liver, which supports our results (Mathes, 2010). On the other hand, lower rates of ROS generation in the liver and decreases in mitochondrial energy metabolism has been reported in rats subjected to hypobaric hypoxia (Costa et al, 1993;NouetteGaulain et al, 2011 andFarías et al, 2005a).…”
Section: Discussionsupporting
confidence: 82%
“…Melatonin has previously been demonstrated to be a powerful protective substance in numerous injury models as ischemia/ reperfusion, where it is cardio-protective in both physiological and pharmacological concentrations. These benefi cial effects have been attributed to the capacity of this hormone to act as a radical scavenger (Kücükakin et al, 2009;Mathes, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of MLT influence on hsp70 expression, though not in the context of photoperiod-associated stress; MLT decreased hsp70 expression in rat brains and mouse CNS as well as in the hepatic tissue (Sharman et al, 2007;Ozacmak et al, 2009;Mathes, 2010). Here, there was a different response of hsp70 mRNA expression to MLT treatment in brain and hepatic tissues: whereas in hepatic tissue hsp70 expression was increased by MLT after SLI, in brain tissue hsp70 expression was decreased.…”
Section: Discussionmentioning
confidence: 40%
“…Using the model of cecal ligation and puncture in rats and mice, a number of researchers were able to demonstrate the beneficial effects of melatonin treatment with respect to skeletal (15,16) or cardiac (17,31,32) mitochondrial dysfunction, as well as regarding survival (9,32), using between 3 and 30 mg/kg melatonin. Further, previous studies on organ protective effects of melatonin after different models of stress show comparable beneficial results for doses between 100 µg/kg and 100 mg/kg melatonin (33). Yet, Maestroni (5) demonstrated that 10 mg/kg melatonin intensely attenuated the improvements of survival observed in septic animals treated with lower doses.…”
Section: Discussionmentioning
confidence: 84%